Pemenuhan Kewajiban Adat dalam Tindak Pidana Kekerasan Seksual - Siregar, Elizabeth; Davega Prasna, Adeb; Rakhmawati, Dessy (Faculty of Law, Universitas Jambi, 2025)
One of the progressiveness of the New Criminal Code that reflects harmonization and adaptation is the recognition of customary law values ​​by including sanctions for fulfilling local customary obligations as additional criminal penalties (Article 66 paragraph 1 letter f). Fulfillment of customary obligations correlates with Article 597 Paragraph 1: In relation to the meaning of